1994
DOI: 10.1038/bjc.1994.241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyunsaturated fatty acids on the growth of murine colon adenocarcinomas in vitro and in vivo

Abstract: S_mary }The effect of the polyunsaturated fatty acids (PUFAs) linoleic acid (LA) and arachidonic acid (AA) on the growth of two murine colon adenocarcinoma cell lines (MAC26 and MAC13) has been determined both in vitro and in vivo. When the serum concentration in the medium became growth limiting, low concentrations (18-33 pM) of both PUFAs were growth stimulatory to both cell lines, while higher concentrations were growth inhibitory. Growth stimulation by AA in both cell lines, and by LA in MAC13, was effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 14 publications
0
16
0
2
Order By: Relevance
“…However, in contrast to our results low concentrations of the n-3 PUFAs, EPA and DHA were growth inhibitory Connolly, 1990, 1991). LA and ARA also stimulated cell proliferation of murine colon adenocarcinomas (Hussey and Tisdale, 1994). Perfusion of Morris hepatomas (7288CTC) in situ with donor whole blood containing added PUFAs resulted in an increased (n-6) or decreased (n-3) rate of DNA synthesis (Sauer and Dauchy, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to our results low concentrations of the n-3 PUFAs, EPA and DHA were growth inhibitory Connolly, 1990, 1991). LA and ARA also stimulated cell proliferation of murine colon adenocarcinomas (Hussey and Tisdale, 1994). Perfusion of Morris hepatomas (7288CTC) in situ with donor whole blood containing added PUFAs resulted in an increased (n-6) or decreased (n-3) rate of DNA synthesis (Sauer and Dauchy, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Brown intracellular vesicles of lipiodol were present in numerous tumour cells, which demonstrated a ballooned, foamy appearance. (Hussey and Tisdale, 1994), and gamma-linoleic acid has been shown to enhance the effect of anticancer treatments (Mudan et al, 1993); linoleic and arachidonic acids are major constituents of lipiodol. Lipiodol is known to localise in human kidney, breast and bladder cancers; further studies are indicated to assess if cellular incorporation of lipiodol occurs in these tumours as well.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, MAC cell lines have been shown to undergo growth stimulation by LA both in vitro and in vivo (Hussey and Tisdale, 1994) and these cell lines show low IC50 values for CV-6504. The oestrogen-independent human breast cancer cell line, MDA-MB-231, is also sensitive to CV-6504.…”
Section: Discussionmentioning
confidence: 99%
“…PUFAs, and LA in particular, have been implicated as tumour promoters (Reddy and Masura, 1984), as enhancers of metastasis and as stimulators of tumour growth in vitro (Wicha et al, 1979) and in vivo (Hussey and Tisdale, 1994). These effects are probably due to metabolism of LA to prostaglandins or products of the lipoxygenase pathways.…”
mentioning
confidence: 99%